Excitotoxicity mediated by Ca2+-permeable GluR4-containing AMPA receptors involves the AP-1 transcription factor - Santos, A. E. (2006)
Cells preferentially expressing GluR4-containing alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptors are particularly sensitive to excitotoxicity mediated through non-N-methyl-D-aspartate receptors. However, the excitotoxic signalling pathways associated with GluR4-containing AMPA receptors are not known. In this work, we investigated the downstream signals coupled to excitotoxicity mediated by Ca2+-permeable GluR4-containing AMPA receptors, using a HEK 293 cell line constitutively expressing the GluR4flip subunit of AMPA receptors (HEK-GluR4). Glutamate stimulation of GluR4-containing AMPA receptors decreased cell viability, in a calcium-dependent manner, when the receptor desensitisation was prevented with cyclothiazide. The excitotoxic stimulation mediated through GluR4-containing AMPA receptors increased activator protein-1 (AP-1) DNA-binding activity. Inhibition of the AP-1 activity by overexpression of a c-Jun dominant-negative form protected HEK-GluR4 cells against excitotoxic damage. Taken together, the results indicate that overactivation of Ca2+-permeable GluR4-containing AMPA receptors is coupled to a death pathway mediated, at least in part, by the AP-1 transcription factor